Keefektifan Konseling Realita Untuk Meningkatkan Pengendalian Perilaku Siswa di SMP - Sinata Sinata (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The aim to be achieved in this study is to determine the effectiveness of Reality Counseling on improving behavioral control of students. The research design used was quasi-experimental. Samples were taken by purposive sampling technique. The number of subjects taken were 5 students who had low behavioral control. Data obtained through the subject, using behavior control inventory that has been tested for validity by using item analysis and reliability testing with alpha r obtained at 0, 766> r table 0, 316. Analysis of the results of the study using nonparametric statistics using the Wilcoxon Signedankank test. From the results of the calculation of different tests with the Wilcoxon formula, the Z wilcoxon value is -2.060 with a probability (p) or significance (α) of 0.039. Because the wilcoxon Z value has a probability (p) or significance (α) of less than 0.05 (p